Agricultural Credit Provided by Financial Institutions in Thailand - Poramacom, Nongnooch (Kasetsart Journal of Social Sciences, 2002)
A research reveals three financial institutions mostly involved in agricultural credit in Thailand: Bank for Agriculture and Agricultural Cooperative (BAAC), commercial banks, and agricultural cooperatives by the secondary data during 1985 to 2,000, using a descriptive method. The BAAC has played an important role providing credit, approximately 63.1 % of total credit in 1999. Commercial banks were second largest share of agricultural credit accounted for 36.9%. BAAC net profit had increased from 140.28 million baht in 1985 and had reached the peak at 1,448.68 million baht in 1997. Then the BAAC net profit had declined overtime. Moreover doubtful accounts had showed an increase since 1996 and had reached the peak at 5,664 million baht in 2000. Net profit of cooperatives at primary level increased from 187.57 million baht in 1985 to 1,782.56 million baht in 2000. While cooperatives at secondary level performed some net loss. Comparison of net profit and doubtful accounts between BAAC and cooperatives at primary level after the economic crisis, the crisis had negative impacts on BAAC. BAAC net profit decreased from 1,448.68 million baht in 1997 to 280.47 million baht in 2000, while cooperatives at primary level still performed an increase net profit. In addition, BAAC doubtful accounts had increased over time, while doubtful accounts of cooperatives at primary level remained the same.